THE EFFECT OF ACCELERATED READING THE QUR'AN USING THE WAFA METHOD TO INCREASE THE DISCIPLINE AND ENTHUSIASM OF THE CHILDREN OF RA AL-AMIN TABANAN BALI - Purnamasari, Ita (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Learning the Koran with media images, is a fun learning for all students. The use of image media, including colorful and pictorial flashcards equipped with hijaiyah writing arranged in a word. Emphasis on the use of everyday language, to maintain students' emotional and moody conditions, keep them enthusiastic and happy while participating in the Teaching and Learning Activities (KBM). The facilities arranged in the form of books for students are modified according to the degree of development and age of the child. The use of the right brain to balance the function of the hemispheres to improve the quality and personality of students is the hallmark of the 'wafa' method. Learning the Koran in the form of reading, writing and memorizing, understanding the meaning and interpreting verses is all taught in 'wafa' in stages and stages. 'Wafa' is often referred to as the right-brain method which in learning uses multisensory aspects or a combination of various senses, such as visual, auditory, and kinesthetic